Factor Structure of the Teacher Autonomy Scale - Borka D. Malčić; Stanislava D. Marić Jurišin; Nataša D. Tančić (University of Belgrade, Teacher Education Faculty, 2023)
Teacher autonomy encompasses in its essence the (self)activity of the teacher, the right and opportunity to make decisions and choices, and finally accepting the consequences that come with those decisions. Accordingly, autonomy represents one of the core competences of the modern teacher and it is being increasingly in the focus of numerous pedagogical researches. The purpose of the study conducted and presented in this paper was to examine psychometric characteristics and determine factor structure of the Teaching Autonomy Scale (TAS). The study sampled 310 teachers of the upper-primary subjects and primary school grade teachers from 16 primary, mixed-sex public schools. The researchers have applied Horn's parallel factor analysis and initially extracted three factors, but due to a low reliability of the third subscale, a shortened version was suggested with two factors and 10 items. The first factor represents Curriculum autonomy, while the second one refers to General autonomy. The conclusion is that the TAS scale can be used in its modified version of 10 items and with a two-factor structure of the instrument.